DECISION STRATEGY TO INCREASE THE MARKET SIZE OF EPLC - Ibrahim, Maulana Malik; Siallagan, Manahan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to improve the decision-making strategies of EPLC’s marketing team through the usage of Analytical Hierarchy Process (AHP). EPLC, an English language learning institution in Bandung, Indonesia, wants to increase its students up to 1000 students. Historical data analysis revealed that there are gaps reaching this target, necessitating improved marketing strategies. The study evaluates four alternatives which are social media campaigns, regular referrals, and alumnus referral program, and a student ambassador program based on some key criterias, cost efficiency, reach, impact, and improvable. Using AHP, social media campaigns rank to be the most effective strategy, followed by the student ambassador program. This research concludes that combining two strategies could maximize the results without interfering with one another. It highlights the importance of decision-making tools, such as AHP, in optimizing marketing strategies for educational institutions.